Human Rights Legal Protection for Child Victims of Sexual Crimes: The Perspective of Aceh's Qanun Jinayat - Rosbayatinur; Onny Medaline (Journal of Indonesian Constitutional Law, 2026)
This study aims to analyze the regulation and implementation of legal protection for child victims of sexual crimes under Qanun Aceh Number 6 of 2014 on Jinayat Law, with particular emphasis on the perspective of human rights protection and Islamic law in Aceh. The study contributes to the development of constitutional and criminal law scholarship by integrating child protection principles, human rights norms, and the doctrinal application of Jinayat Law in judicial practice, particularly through the analysis of Decision Number 5/JN/2026/MS.Aceh. This research employs a normative juridical method with a case approach, relying on statutory analysis, human rights instruments, Islamic legal principles, and judicial reasoning. The findings show that the Jinayat framework provides formal legal protection for child victims through the criminalization of sexual harassment and rape, as well as through ta’zir sanctions. However, the practical application of protection remains strongly dependent on the strict interpretation of statutory elements, especially the requirement of penetration in rape cases. From a human rights perspective, such protection must not only ensure legal certainty and punishment, but also guarantee the dignity, recovery, and best interests of the child as a vulnerable rights-holder. The study concludes that legal protection for child victims in Aceh requires a more child-centered and rights-based interpretation. It recommends strengthening harmonization between the Jinayat law, the national child protection law, and international human rights standards in order to ensure more comprehensive protection for child victims of sexual crimes.